(untitled) (Cadernos de Sociomuseologia, 2017)
This paper It shows the interconnections between the museological display and the poetics of Manoel de Barros (1916-2014), Brazilian writer whose proposal is to disinvent objects and distort the look. In this respect, as the poet strategy, the exhibition approaches different things, fragmented trajectories and taken from their original function are placed in a new context resulting from a poetic gesture (syntax of things). Our aim is to investigate to what extent the poetic alchemy promoted by exhibitions and the poetics and politics of museums promoted by Sociomuseology consist of ways to institute a new dramaturgy of the memory. Keywords: Museology,exhibitions,poetics,Manoel de Barros.